Sebaceous Carcinoma of the Eyelid Mimicking as Squamous Cell Carcinoma: A Histopathological Dilemma - Bhattarai, Samiksha; Lavaju, Poonam; Shah, Sangeeta; Agrawal, Yamuna (Journal of BP Koirala Institute of Health Sciences, 2024)
Sebaceous carcinoma is a rare malignant tumor of the skin, mostly seen in eyelids. Periocular sebaceous carcinoma can clinically mimic a variety of conditions and is often misdiagnosed as basal cell or squamous cell carcinoma. Here, we present a case of 56-year- old- female who presented with a slow growing lesion over the left upper eye lid with irregular margin and extensive upper tarsus involvement for a duration of one year. An incisional biopsy of the lesion revealed Squamous Cell Carcinoma. She underwent wide local excision along with Culter Beard procedure for eyelid reconstruction. However, histopathological examination of the excisional biopsy revealed findings suggestive of Sebaceous Carcinoma. Therefore, this report highlights the importance of understanding the various histopathological findings seen in sebaceous carcinoma and the significance of its meticulous management.